Prayer Bead Gestures and Television: A Case Study on Cultural Inspirations for Interaction Art Education - Ozcan, Oguzhan; Akdemir, Eme; O'Niel, Mary Lou; Unlur, A. Ayca (MIT PRESS, 2009)
The authors, interactive design-art educators, recount their experience in using cultural inspirations as part of student exercises. The authors found that, although students proposed various design concepts drawing from the surrounding culture, very few moved beyond experience design art. In order to remedy this situation without giving explicit direction, the authors encouraged students to examine cultural habits and/or artifacts from their past or their current lives in the hope that this could generate innovative design ideas. One such project is the Prayer Bead Gesture Based TV Input Device.
Keywords: Art